2023
DOI: 10.1177/09636897231186063
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Duration of Pretreatment Using a Gelatin Hydrogel Nonwoven Fabric Prior to Subcutaneous Islet Transplantation

Abstract: Subcutaneous islet transplantation is a promising treatment for severe diabetes; however, poor engraftment hinders its prevalence. We previously revealed that a gelatin hydrogel nonwoven fabric (GHNF) markedly improved subcutaneous islet engraftment in comparison with intraportal islet transplantation. We herein investigated whether the duration of pretreatment using GHNF affected the outcome of subcutaneous islet transplantation. A silicone spacer with GHNF was implanted into the subcutaneous space of healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Patikova et al reported that the ideal timing of islet transplantation, when the capillary network and collagen synthesis are maximized, is important for islet engraftment [ 27 ]. We also reported that the length of the GHNF-pretreatment period had a strong impact on the results of subcutaneous islet transplantation and that six weeks was the best duration when neovascularization was maximized and inflammatory reactions were minimized in a mouse model [ 12 ]. However, the extent of absorption of GHNF varies among animal species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patikova et al reported that the ideal timing of islet transplantation, when the capillary network and collagen synthesis are maximized, is important for islet engraftment [ 27 ]. We also reported that the length of the GHNF-pretreatment period had a strong impact on the results of subcutaneous islet transplantation and that six weeks was the best duration when neovascularization was maximized and inflammatory reactions were minimized in a mouse model [ 12 ]. However, the extent of absorption of GHNF varies among animal species.…”
Section: Discussionmentioning
confidence: 99%
“…GHNF has been reported to be absorbed in vivo and replaced by recipient cells and ECM [ 17 ]. We previously reported that M2 macrophages, which have anti-inflammatory properties [ 32 ], accumulated between the gaps of GHNF [ 12 ]. The concentration of insulin-like growth factor-2, which maintains islet viability and has anti-apoptotic effects on islets [ 33 , 34 ], in the subcutaneous space, is high in the GHNF group in a mouse model [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations